STRATEGI PEMBELAJARAN MENDALAM DALAM PENGEMBANGAN KETERAMPILAN MENULIS KONTEN DIGITAL DI MEDIA SOSIAL - Mubaraq, Syahrul; Rias Ramlan, Andi; Maulana, A. Aril; Candra Dewi, Anita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study, entitled "Deep Learning Strategies in Developing Digital Content Writing Skills on Social Media," aims to analyze how deep learning strategies play a role in developing digital content writing skills in the community. This study used a qualitative method with a descriptive approach to explore individuals' experiences, processes, and actual practices in writing on social media. Data were obtained through observation and questionnaires using a purposive sampling technique from active social media users. The results showed that digital content writing activities reflect deep learning principles, such as cognitive engagement, reflection, and experience-based meaning construction. Respondents not only wrote spontaneously but also considered the audience, message clarity, and presentation context, indicating the presence of critical thinking processes. However, obstacles were still encountered such as difficulty finding ideas, choosing diction, and low self-confidence. The conclusion of this study confirms that deep learning strategies are relevant and effective in optimizing digital content writing skills, so that writing activities on social media can function as a meaningful and sustainable learning process.